Interaction of platelets with liposomes containing dodecapeptide sequence from fibrinogen - Nishiya, Takako; Toma, Chikaho (Thrombosis and Haemostasis, 2004)
Liposomes with a covalently bound synthetic peptide containing the dodecapeptide sequence HHLGGAKQAGDV, the putative platelet interaction site at γ400-411 of fibrinogen (dodecapeptide-liposomes), were prepared. These liposomes enhanced platelet aggregation and specifically adhered to platelets activated on the collagen surface. Dodecapeptide-liposomes released encapsulated materials upon interacting with platelets activated on the collagen surface.The rate of content release was dependent on the peptide surface density, indicating that the interaction between the dodecapeptide-liposomes and platelets activated on the collagen surface induces clustering of the surfacecoupled ligands at the binding site on the receptor matrix to facilitate release of the internal contents through the liposome membranes. The level of lipid mixing between the dodecapeptide-liposomes and platelets activated on the collagen surface was relatively low, however it was increased in liposome preparations containing octa-arginine, the (R)8GDV sequence, while content release was maintained at the same level as that of the dodecapeptide-liposomes. The level of content release and lipid mixing for liposome preparations containing the RGD sequence as a ligand (RGD-liposomes) upon interacting with platelets activated on the collagen surface was extremely low. Both the level of the content release and lipid mixing, however, were enhanced in liposome preparations containing octa-arginine, the (R)8RGD sequence. Dodecapeptide-liposomes and RGD-liposomes were not internalized by activated platelets. On the other hand, liposomes containing (R)8PPQ, (R)8RGD, or (R)8GDV were internalized by activated platelets, and the extent of internalization was inversely related to ligand affinity to the target.
Keywords: Liposome-platelet interaction; peptide-conjugated liposome; platelet substitute; dodecapeptide; octa-arginine